Room and high-temperature tensile properties of austenitic stainless steel 321 fabricated by wire arc additive manufacturing - A. Rajesh Kannan; N. Siva Shanmugam; K. Sanjeeviprakash; Yasam Palguna; Rajesh Korla; Wonjoo Lee; YuHyeong Jeong; Jonghun Yoon (Journal of Materials Research and Technology)
SS 321 is a potential structural alloy for elevated temperature applications. In this work, austenitic stainless steel 321 (SS 321) was successfully fabricated via wire arc additive manufacturing (WAAM). Microstructural analysis of the wrought SS 321 revealed the presence of equiaxed grains. In contrast, the WAAM 321 wall structure comprised equiaxed, columnar, and elongated dendrites with ferrite fractions ranging from 3.6 to 5.9 FN. Further, the WAAM 321 exhibited better hardness than the wrought alloy. WAAM 321 samples exhibited excellent tensile properties compared to the SS 321 wrought alloy, while the tensile strength and ductility decreased considerably from room temperature (RT) to elevated temperatures (900 °C). The average tensile strength of SS 321 at 900 °C was 108 ± 6 MPa, and the WAAM 321 samples showed higher strength (∼135 ± 7 MPa). The decrease in tensile strength is attributed to the activation of a multi-slip system, resulting in a lower resistance to dislocation motion at elevated temperatures. Also, serrated yielding was observed at 600 °C due to dynamic strain aging. The fractured surface characteristics align with the ductility trend. This research highlights the role of WAAM in manufacturing high-performing structures for elevated temperature environments.